Environmental Innovation in Germany - Haščič, Ivan (OECD Environment Working Papers, 2012)
This paper reviews the recent experience of Germany in encouraging innovation to reduce negative environmental impacts of economic activity. The essence of the German approach to policy-induced environmental innovation is discussed in the context of changing policy objectives, and illustrated with selected examples from waste management, renewable energy and transportation. The paper covers environmental and general innovation policies and the cross-cutting issue of policy co-ordination. Particular attention is paid to analysis of policies to promote renewable energy, including feed-in tariffs, and policies to promote advanced transportation